Beyond East and West: the Meaning and Significance of Kim’s Great Game (Altre Modernità, 2014)
In his essay Wilson also inaugurates the fortunate metaphor of East and West(epitomised by the lama Teshoo and Colonel Creighton) as parallel worlds that nevermeet, less than ever at the end of the novel. Subsequent criticism, including Said’shighly influential introduction to the Penguin edition of Kim